Highly Stable Polymer Solar Cells Based on Poly(dithienobenzodithiophene-co-thienothiophene) - Shin, Nara; Yun, Hui-Jun; Yoon, Youngwoon; Son, Hae Jung; Ju, Sang-Yong; Kwon, Soon-Ki; Kim, BongSoo; Kim, Yun-Hi (AMER CHEMICAL SOC, 2015)
It is important to develop new denor (D)acceptor (A) type low band gap polymers for highly stable polymer solar cells (PSCs). Here, we describe the synthesis and photovoltaic properties of two D-A type low band gap polymers. The polymers consist of dithienobentodfthiophene (DTBDT) moieties with expanded conjugation side: groups as donors and 2-ethyl-1-(thieno[3,4-b]thiophen-2yl)hwtan-1-one (TTEH) or 6-octyl-5H-thieno[3',4':4,5]thieno[2,3-c]pyrrole-5,7(6H)-dione (DTPD) as acceptors to give pDTBDT-TTEH and pDTBDT-DTPD polymers, respectively. The pDTBDT-TTEH is quite flat, resulting in a highly crystalline film. In contrast, the pDTBDT-DTPD is highly twisted to yield an amorphous film. Photovoltaic devices based on pDTBDT-TTEH and pDTBDT-DTPD exhibited power conversion efficiencies (PCEs) of 6.74% and 4.44%, respectively. The PCE difference results mainly from morphological differences between the two polymer:PC71BM blend films; the pDTBDT-TTEH polymer formed a nanoscopically networked domains in the blend state, while the pDTBDT-DTPD polymer film contained aggregated domains with large phase separation between the poly-mer and PC71BM molecules. Importantly, we observed that pDTBDT-TTEH-based devices showed excellent stability-in air, retaining 95% of the initial PCE after storage for over 1000 h without encapsulation. The high stability of the pDTBDT-TTEH-based device was originated mainly by the crystalline nature of the pDTBDT-TTEH:PC71BM film. This work suggests that designing highly conjugated planar backboned polymers is crucial to improve not only the photovoltaic performance but also the stability of PSCs.
Keywords: BAND-GAP POLYMERS; EFFICIENCY; COPOLYMERS; AGGREGATION; SUBSTITUENT; TRANSPORT; BLEND